Indian consensus statements on the management of small renal masses, non‐muscle invasive bladder cancer and high‐risk/locally advanced prostate cancer - Simon Hughes; Rajesh Nair; Bhav Radia; Ravimohan S. mavuduru; Prokar Dasgupta; Amit Ghose (BJUI Compass)
Abstract No pan‐India‐specific guidelines exist for the management of urological cancers. Although western guidelines are useful for informing management strategies, they do not account for the nuances of management in the Indian context. A modified Delphi method was used to provide a framework for the systematic development of India‐centric guidelines for the management of three uro‐oncology disease states: small renal masses, non‐muscle invasive bladder cancer and high‐risk/locally advanced prostate cancer.